Inside Cover: Three‐Dimensional Coral‐Like Structure Constructed of Carbon‐Coated Interconnected Monocrystalline SnO2 Nanoparticles with Improved Lithium‐Storage Properties (ChemElectroChem 7/2016). Issue 7 (27th June 2016) - Xu, Wangwang; Cui, Xiaodan; Xie, Zhiqiang; Dietrich, Grant; Wang, Ying
Abstract : The Inside Cover picture shows the three‐dimensional coral‐like nanostructure constructed from carbon‐coated interconnected monocrystalline SnO2 nanoparticles. Owing to such unique composite 3D coral‐like structure, lithium ions and electrons can access SnO2 easily, leading to remarkably large capacity at high rate for applications in lithium‐ion batteries. More details can be found in the Full Paper by Y. Wang and co‐workers onpage 1098 in Issue 7, 2016 (DOI:10.1002/celc.201600131 ).